Germany can increase its raw material import security of supply - Lukas Menkhoff; Marius Zeevaert (DIW Weekly Report, 2022)
Over 90 percent of Germany's raw materials supply is imported and many of these imports come from only a small handful of producer countries. Often, these producer countries tend to be less democratic. In this respect, supply risks are extremely high in some cases, including for mineral raw materials such as rare-earth elements, lithium, and magnesium. To increase raw material import security of supply, various economic policies can be undertaken. European customers could bundle their procurement of raw materials to counter the market power of the few suppliers and more diversification potentials in imports could be used. Raw material storage should also be reconsidered and supplemented by a mandatory minimum reserve. In the long term, raw material imports can be reduced by recycling more and expanding domestic mineral raw material production. Finally, technical innovations should be initiated to replace raw material imports. These measures should be coordinated at a European level as much as possible.
Keywords: F14; F52; Q37; 330; raw material imports; national security; vulnerability; diversification